insert the parentheses in expresion 2 so that it has value of 19 then show why your expression has value of 19
![insert the parentheses in expresion 2 so that it has value of 19 then show why your expression has value of 19 class=](https://us-static.z-dn.net/files/d92/3ff93f55e110d24780dab0abb183de5c.png)
(a) What is the value of Expression 1?
Expression 1: 6 * 7 - 3^2 * 9 + 4^3
6 * 7 - 3^2 * 9 + 4^3
= 42 - 81 + 64
= 25
(b) Insert parentheses in Expression 2 so that it has a value of 19. Then show why your expression has a value of 19.
Expression 2: 5 + 4 * 2 + 6 - 2 * 2 -1
(5 + 4) * 2 + 6 - (2 * 2) -1
= 9*2 + 6 - 4 - 1
= 18 + 6 - 5
= 24 -5
= 19